Moramonas marocensis gen. nov., sp. nov.: a jakobid flagellate isolated from desert soil with a bacteria-like, but bloated mitochondrial genome. Issue 2 (February 2016) - Strassert, Jürgen F. H.; Tikhonenkov, Denis V.; Pombert, Jean-François; Kolisko, Martin; Tai, Vera; Mylnikov, Alexander P.; Keeling, Patrick J.
Abstract : A new jakobid genus has been isolated from Moroccan desert soil. The cyst-forming protist Moramonas marocensis gen. nov., sp. nov. has two anteriorly inserted flagella of which one points to the posterior cell pole accompanying the ventral feeding groove and is equipped with a dorsal vane—a feature typical for the Jakobida. It further shows a flagellar root system consisting of singlet microtubular root, left root (R1), right root (R2) and typical fibres associated with R1 and R2. The affiliation of M. marocensis to the Jakobida was confirmed by molecular phylogenetic analyses of the SSU rRNA gene, five nuclear genes and 66 mitochondrial protein-coding genes. The mitochondrial genome has the high number of genes typical for jakobids, and bacterial features, such as the four-subunit RNA polymerase and Shine–Dalgarno sequences upstream of the coding regions of several genes. The M. marocensis mitochondrial genome encodes a similar number of genes as other jakobids, but is unique in its very large genome size (greater than 264 kbp), which is three to four times higher than that of any other jakobid species investigated yet. This increase seems to be due to a massive expansion in non-coding DNA, creating a bloated genome like those of plant mitochondria.